Behavioral Finance In Investment Decisions - Asbaruna, Latifah Wulandari Binti; Gorib, Ridwan Ismail; Syifa, Muhammad Akbar Ali (Research Collaboration Community (Rescollacom), 2023)
Behavioral finance has an important role in finance, namely understanding human behavior, including investor behavior. The type of data used is secondary data, namely data that is not directly given to data collectors, this data is obtained from books, scientific articles and internet sites, materials related to behavioral finance. The data collection technique in this study is a literature study that is directly related to behavioral finance. The method used in this research is the Systematic Literature Review (SLR), where the results of this study try to map the trends that occur regarding behavioral finance, also try to predict where this research will go, so that later it is expected to provide new input and views for the world of behavioral finance, what what needs to be explored at this time, what contributions are needed at this time, and can be an attraction for other researchers to study behavioral finance.